Inclusion of Health Equity Initiatives in Hospitals' Strategic Plans (Mary Ann Liebert, 2023)
Objective: This study examined the health equity initiatives included in US hospitals' strategic plans. Methods: Using data from the American Hospital Association (AHA) 2021 Annual Survey, the study described the types of health equity initiatives that US hospitals included in their strategic plans. The analysis focused on the following seven initiatives: (1) equitable and inclusive organizational policies; (2) systematic and shared accountability for health equity; (3) diverse representation in hospital and health care system leadership; (4) diverse representation in hospital and health care system governance; (5) community engagement; (6) collection and use of segmented data to drive action; and (7) culturally appropriate patient care. Logit and zero-truncated Poisson regression analysis was used to examine organizational and community-level characteristics of hospitals with the most comprehensive health equity strategic plans. Results: Of the 4359 general medical and surgical hospitals that completed the AHA's 2021 survey, 45.1% provided complete information on their health equity strategies. The comprehensiveness of hospitals' health equity efforts varied across organizations. Regression analysis showed that larger hospitals, nonprofit hospitals, and hospitals affiliated with health systems tended to have more comprehensive health equity initiatives as did hospitals located in urban areas, hospitals in communities with higher household incomes, and hospitals in communities with greater proportions of Hispanic residents. Conclusions: While improving health and health equity is a key aspect of many hospitals' missions, the extent to which hospitals include health equity initiatives into their strategic plans varied noticeably. Committing to a comprehensive set of efforts aimed at improving health equity requires human and financial resources as well as dedicated leadership.